Efektivitas Terapi Mindfulness Berbasis Aplikasi Breathe2Relax Terhadap Stres Mahasiswa Tingkat Akhir - Mira Agusthia; Utari Christya Wardhani; Novita Rochmayanti; Triyana Harlia Putri (Universitas Malahayati Lampung, 2024)
ABSTRACT Academic stress is defined as a condition of individuals experiencing pressure from the perception and assessment of academic stressors, which are related to science and education in higher education. The prevalence of students in the world who experience stress is 38-71%. Meanwhile, the prevalence of students experiencing stress in Indonesia was 36.7-71.6%. Stress cannot be prevented but it can be managed. Non-pharmacological therapy for stress reduction is application-based mindfulness. The “Breathe2Relax” app is also a portable skill training tool for practicing diaphragmatic breathing. Mindfulness brings students to focus on realizing the conditions they are currently facing, accepting them with sincerity, without reacting and giving judgments. To determine the effectiveness of Mindfulness Therapy based on the Breathe2Relax Application on Final Year Student Stress. Quantitative research quasi-experimental one group pretest - posttest design without a control group and sampling using purposive sampling with a total sample of 34 students. The level of stress before being given mindfulness therapy was moderate stress as many as 32 people (94.1%) and severe stress as many as 2 people (5.9%). The stress level of students after being given mindfulness therapy was 29 people (85.3%) mild stress and 5 people (14.7%) moderate stress. The results of the analysis test showed that there was an effectiveness of mindfulness therapy based on the Breathe2Relax application on stress in final year students at Awal Bros University. p value=0.000 (p0.05). There is an effect of the effectiveness of mindfulness therapy based on the